Auditory and Visual Electrophysiology of Deaf Children with Cochlear Implants: Implications for Cross-modal Plasticity - Corina, David P.; Blau, Shane; LaMarr, Todd; Lawyer, Laurel A.; Coffey-Corina, Sharon (Frontiers in Psychology, 2017)
Deaf children who receive a cochlear implant early in life and engage in intensive oral/aural therapy often make great strides in spoken language acquisition. However, despite clinicians’ best efforts, there is a great deal of variability in language outcomes. One concern is that cortical regions which normally support auditory processing may become reorganized for visual function, leaving fewer available resources for auditory language acquisition. The conditions under which these changes occur are not well understood, but we may begin investigating this phenomenon by looking for interactions between auditory and visual evoked cortical potentials in deaf children. If children with abnormal auditory responses show increased sensitivity to visual stimuli, this may indicate the presence of maladaptive cortical plasticity. We recorded evoked potentials, using both auditory and visual paradigms, from 25 typical hearing children and 26 deaf children (ages 2-8 years) with cochlear implants. An auditory oddball paradigm was used (85% /ba/ syllables vs. 15% frequency modulated tone sweeps) to elicit an auditory P1 component. Visual evoked potentials (VEPs) were recorded during presentation of an intermittent peripheral radial checkerboard while children watched a silent cartoon, eliciting a P1-N1 response. We observed reduced auditory P1 amplitudes and a lack of latency shift associated with normative aging in our deaf sample. We also observed shorter latencies in N1 VEPs to visual stimulus offset in deaf participants. While these data demonstrate cortical changes associated with auditory deprivation, we did not find evidence for a relationship between cortical auditory evoked potentials and the visual evoked potentials. This is consistent with descriptions of intra-modal plasticity within visual systems of deaf children, but do not provide evidence for cross-modal plasticity. In addition, we note that sign language experience had no effect on deaf children’s early auditory and visual ERP responses.